Stakeholder Collaboration in Revitalising Peneleh Heritage Tourism Area in Surabaya: A Pentahelix Perspective - Hidayat, Syahrul; Pramudya, Wisnu (Journal of Tourism Sustainability, 2025)
This study investigates the dynamics of multi-stakeholder collaboration in the revitalisation of the Peneleh heritage tourism area in Surabaya, Indonesia, addressing a notable research gap concerning the empirical application of collaborative governance models—particularly the pentahelix framework—within the context of urban heritage tourism. Adopting a qualitative case study design suited for exploring complex stakeholder interactions, the research draws upon in-depth interviews, document analysis, and field observations to construct a comprehensive understanding of the collaborative process. Thematic analysis reveals six interrelated dimensions of collaboration: idea co-creation, participatory decision-making, capacity building, joint implementation, sustainability efforts, and tangible revitalisation outcomes. The findings suggest that collaborative engagement not only facilitated the physical restoration of heritage assets but also reinforced socio-cultural identity and stimulated local economic vitality through community-driven microenterprises. Theoretically, this study contributes to refining the pentahelix model by elucidating the evolving and strategic roles of the business sector, media, and community actors in fostering public engagement, mobilising resources, and enhancing market access—dimensions often underemphasised in existing frameworks. Practically, it underscores the necessity of inclusive governance structures, continuous multi-channel communication, and shared resource mechanisms to ensure the sustainability of urban heritage regeneration. The insights generated offer actionable guidance to policymakers and practitioners developing participatory models to revitalise culturally significant urban areas.